(untitled) (Global Journal of Management and Business Research, 2016)
Women’s economic empowerment is very much important part of economic development discourse in any development undertaking of a nation. Women empowerment depends on taking part in various development activities. Therefore, the involvement of women in various entrepreneurial activities has empowered them in social, economic and cultural fields. Despite recent progress in the advancement and empowerment, women in Bangladesh still remain vulnerable to poverty and social deprivations. Women entrepreneurs are in a less favorable position compared to men in case of accessing for example commercial credit from formal financial service providers, more lucrative markets, rather than the traditional local markets, technology and information to establish and grow their businesses, national incentives in small enterprise development through gender blind private sector development and fiscal policies and legislation and training and education for small enterprise development. In such a context, this paper attempts to investigate, evaluate and analyze the available support services for developing women entrepreneurship in Bangladesh.